AB0857 Single nucleotide polymorphisms associated with non response to anti-TNF-alpha treatment in ankylosing spondylitis patients. Data from regisponser. (23rd January 2014) - Schiotis, R.; Sánchez, A.; Bartolomé, N.; Szczypiorska, M.; Sanz, J.; Martínez, A.; Tejedor, D.; Artieda, M.; Mulero, J.; Font, P.; Escudero, A.; Buzoianu, A.; et al.
Abstract : Background: Taking into account that almost 40% of AS patients remain disease active even on long term biological treatment 1, genetic biomarkers that differentiate between responders and non-responders would be useful in selecting the apropiate treatment. Objectives: The aim of the study was to investigate candidate single nucleotide polymorphisms (SNPs) responsible for non response to TNF-alpha blockers in Spanish AS patients at the beginning of the first anti- TNF-alpha agent. Methods: We undertook an association study on AS patients enrolled in the REGISPONSER. The patients were classified as "non-responders" if they failed to achieve BASDAI50 improvement criteria at the visit that followed treatment initiation. We selected candidate SNPs which were previously described as associated with susceptibility or pathogenesis of AS and/or other spondylartropathies. SNP genotyping was performed using the Illumina Golden gate genotyping platform. Statistical analysis was performed with the SPSS v19.0 and the SVS v7.3.1 softwares.P-values of <0, 05 were considered statistically significant. Results: Among 121 patients who fulfilled the inclusion criteria, 68 (56.2%) were responders and 53(43.8%) were non-responders.The mean age of studied patients was 47.7 years (±9.5), with mean disease duration since first symptoms of 21.1 years (±8.9). There were no significant differences in baseline clinical and demographic characteristics in the two treatment response groups. From the 345 SNPs tested for association with treatment response status, 10 polymorphisms remained associated after adjustment for multiple testing. Risk alleles of SNPs associated with non-response to anti-TNF-alpha treatment by their OR with 95% confidence intervals (CI) are listed in table 1 . Conclusions: Our study identified 10 different polymorphisms in 10 different genes associated with non response to TNF-alpha blockers. Validation of these markers in further cohorts would be of great interest to confirm the robustness of our results. References: Baraliakos X, Listing J, Fritz C, et al. Persistent clinical efficacy and safety of infliximab in ankylosing spondylitis after 8 years – early clinical response predicts long-term outcome. J. Rheumatology (Oxford). 2011 Sep;50(9):1690-9. Disclosure of Interest: None Declared